Care at critical care medical centers is associated with improved outcomes in patients with accidental hypothermia: a historical cohort study from the J‐Point registry. Issue 1 (27th October 2020) - Fujimoto, Yoshihiro; Matsuyama, Tasuku; Morita, Sachiko; Ehara, Naoki; Miyamae, Nobuhiro; Okada, Yohei; Jo, Takaaki; Sumida, Yasuyuki; Okada, Nobunaga; Watanabe, Makoto; Nozawa, Masahiro; Tsuruoka, Ayumu; et al.
Abstract : Aim: The recommendation that patients with accidental hypothermia should be transported to specialized centers that can provide extracorporeal life support has not been validated, and the efficacy remains unclear. Methods: This was a multicenter retrospective cohort study of patients with a body temperature of ≤35°C presenting at the emergency department of 12 hospitals in Japan between April 2011 and March 2016. We divided the patients into two groups based on the point of care delivery: critical care medical center (CCMC) or non‐CCMC. The primary outcome of this study was in‐hospital death. In‐hospital death was compared using a multivariable logistic regression analysis. Subgroup analyses were carried out according to patients with severe hypothermia (<28°C) or systolic blood pressure (sBP) of <90 mmHg. Results: A total of 537 patients were included, 413 patients (76.9%) in the CCMC group and 124 patients (23.1%) in the non‐CCMC group. The in‐hospital death rate was lower in the CCMC group than in the non‐CCMC group (22.3% versus 31.5%, P  < 0.001). The multivariable logistic regression analysis showed that the adjusted odds ratio (AOR) of the CCMC group was 0.54 (95% confidence interval, 0.32–0.90). In subgroup analyses, patients with systolic blood pressure <90 mmHg in the CCMC group were less likely to experience in‐hospital death (AOR 0.36; 95% CI, 0.23–0.56). However, no such association was observed among patients with severe hypothermia (AOR 1.08; 95% CI, 0.63–1.85). Conclusions: Our multicenter study indicated that care at a CCMC was associated with improved outcomes in patients with accidental hypothermia. Abstract : Care at a critical care medical center is associated with improved outcomes in patients with accidental hypothermia. In subgroup analyses, shock was associated with poor outcomes of accidental hypothermia. Optimizing the transport of patients with accidental hypothermia to a specialized center is likely to be beneficial.